The Optimal Dispatch for a Flexible Distribution Network Equipped with Mobile Energy Storage Systems and Soft Open Points - Yu Ji; Ying Zhang; Lei Chen; Juan Zuo; Wenbo Wang; Chongxin Xu (Energies)
This paper proposes a flexible distribution network operation optimization strategy considering mobile energy storage system (MESS) integration. With the increasing penetration of renewable energy in power systems, its stochastic and intermittent characteristics pose significant challenges to grid stability. This study introduces an MESS, which has both spatial and temporal controllability, and soft open point (SOP) technology to build a co-scheduling framework. The aim is to achieve rational power distribution across spatial and temporal scales. In this paper, a case study uses a regional road network in Chengdu coupled with an IEEE 33-node standard grid, and the model is solved using the non-dominated sorting genetic algorithm III (NSGA-III) algorithm. The simulation results show that the use of the MESS and SOP co-dispatch in the grid not only reduces the net loss and total voltage deviation but also obtains considerable economic benefits. In particular, the net load peak-to-valley difference is reduced by 20.1% and the total voltage deviation is reduced by 52.9%. This demonstrates the effectiveness of the proposed model in improving the stability and economy of the grid.